LINGUOCULTURAL IMPORTANCE OF PHRASEOLOGICAL UNITS IN UZBEK AND ENGLISH THAT REPRESENT THE IDEAS OF TIME AND SPACE (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the comparative linguocultural characteristics of phraseological units (PUs) that embody the fundamental categories of Time and Space in English and Uzbek. By examining the metaphorical and metonymic foundations of these idioms, the study highlights how historical, geographical, and social factors shape the linguistic worldview of each culture. The research identifies both universal cognitive patterns and language-specific nuances that reflect the unique cultural code of English and Uzbek speakers.
Keywords: Phraseology, linguoculturology, concept, time, space, English, Uzbek, comparative Linguistics.